2000
DOI: 10.1017/s0030605300031380
|View full text |Cite
|
Sign up to set email alerts
|

Health considerations of the rehabilitation of illegally traded houbara bustards Chlamydotis undulata macqueenii in the Middle East

Abstract: There is a large illegal trade in trapped houbara bustards Chlamydotis undulata macqueenii, which are smuggled into the Middle East for falconry. Mortality is high and is associated with poor transport conditions, malnutrition, overcrowding and exposure to multiple infectious diseases, in particular aspergillosis, avian pox and paramyxovirus type 1 virus. Other pathogens include Salmonella sp., Pseudomoims sp., Trichomonas sp., intestinal endoparasites, avian leucosis, reovirus, adeno-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…However, it was not possible to assess how these Houbara bustards contracted infection. Presumably, they became in contact with some infected birds during transit, as these birds are illegally transported in very poor conditions, including mingling of a variety of different bird species (Bailey et al, 2000). Interestingly, the Houbara bustard and falcon isolates showed high genetic homologies with A/H5N1 viruses circulating in the wild birds during the same year in Central Europe, indicating that the same genotype was actively circulating and widespread in 2007.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it was not possible to assess how these Houbara bustards contracted infection. Presumably, they became in contact with some infected birds during transit, as these birds are illegally transported in very poor conditions, including mingling of a variety of different bird species (Bailey et al, 2000). Interestingly, the Houbara bustard and falcon isolates showed high genetic homologies with A/H5N1 viruses circulating in the wild birds during the same year in Central Europe, indicating that the same genotype was actively circulating and widespread in 2007.…”
Section: Discussionmentioning
confidence: 96%
“…The Arabs have a fascination for this bird, as it is one of the traditional quarries for falconers since ancient times. The free-living Houbara bustards are trapped from countries such as Pakistan, Iran and Afghanistan and illegally exported to Middle East countries where they are used by falconers to train their falcons (Bailey et al, 2000). In recent decades, there has been a drastic decline in the population of Houbara bustards because of overhunting and habitat degradation.…”
Section: Introductionmentioning
confidence: 99%
“…31 A recent survey of live and dead smuggled birds from 1992-99 revealed that 23.7% of the birds had pox lesions. 10 The cutaneous form causes mild to moderate signs, 10,32 whereas the less commonly seen diphtheritic form causes signs and lesions that are more severe. 31 This latter form of the disease is characterized by the presence of diphtheritic lesions of the upper-digestive and respiratory tracts.…”
Section: Avian Poxmentioning
confidence: 98%
“…Aggravating the situation is the fact that large numbers of birds die during transport to such markets as the result of poor husbandry, crowded transport conditions, insufficient food and water, and exposure to a variety of infectious diseases such as Newcastle disease and avian pox. 8,10 …”
Section: Factors Contributing To the Decline Of The Macqueen's Bustardmentioning
confidence: 99%
See 1 more Smart Citation